1994
DOI: 10.1136/jcp.47.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the matrix metalloproteinases stromelysin, gelatinases A and B, and collagenase in Crohn's disease and normal intestine.

Abstract: Aims-To investigate the role of the matrix metalloproteinases (MMPs) in the connective tissue changes seen in the intestine in Crohn's disease. Methods-Indirect immunofluorescence microscopy using specific antibodies to the MMPs (collagenase, gelatinase A and B, and stromelysin) were used to assess the distribution of these enzymes in normal and diseased intestine. Results-In normal intestine the matrix metalloproteinases were confined to a few isolated inflammatory cells, but in Crohn's disease, the inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
79
1
16

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 13 publications
8
79
1
16
Order By: Relevance
“…However, we were unable to confirm the presence of plasmin in the inflamed tissue. Increased MMP-9 and unchanged MMP-2 expression corroborated the findings of a previous immunohistochemical study, 6 which was unable to distinguish pro-and activated forms. The recent work of Baugh et al 7 clearly shows that MMP-9 is a major factor in human intestinal inflammation, and was assumed to be a product of neutrophilia.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, we were unable to confirm the presence of plasmin in the inflamed tissue. Increased MMP-9 and unchanged MMP-2 expression corroborated the findings of a previous immunohistochemical study, 6 which was unable to distinguish pro-and activated forms. The recent work of Baugh et al 7 clearly shows that MMP-9 is a major factor in human intestinal inflammation, and was assumed to be a product of neutrophilia.…”
Section: Discussionsupporting
confidence: 79%
“…In particular, matrix metalloproteinases (MMPs) -9 and -3 have been associated with mucosal damage and fistulae in Crohn's disease patients, 6,7 MMPs 1, 3, and 13 with intestinal ulcer stroma, and MMPs 10 and 11 with the epithelium. 8,9 Furthermore, CD4 ϩ T cell activation in fetal intestinal explants equated with increased levels of MMP-1 and MMP-3, and exogenous MMP-3 promoted tissue degradation 10 implying a causal role.…”
mentioning
confidence: 99%
“…The gelatinases A (MMP-2) and B (MMP-9) have been shown to be highly upregulated in small as well as large intestinal inflammation in mice and men [11][12][13][14][15][16]. We have recently reported that selective blockage of gelatinases by the synthetic compound RO28-2653 was effectively ameliorating acute ileitis [17] and colitis [18].…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models of Th1-type inflammation (e.g. rheumatoid arthritis, atherosclerosis and colitis) [7][8][9][10] as well as in humans with inflammatory bowel diseases (IBDs) such as ulcerative colitis and Crohn's disease [11][12][13][14][15][16], levels of gelatinases A (MMP-2) and B (MMP-9) are increased in inflamed tissue sites.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MMP9 activity is correlated with active inflammation associated with fistula formation (43, 48). In addition, MMP9 tissue and serum levels correlate with disease activity in UC (1,28,35).In this study we utilized MMP9 transgenic mice (Tg-villin-MMP9) generated specifically to express MMP9 in intestinal epithelium to examine the role and underlying mechanism by which MMP9 modulates the pathogenesis of both infectious and chemical-induced colitis. …”
mentioning
confidence: 99%